DNA methylation during development - Cedar, Howard (Henry Stewart Talks, 2010)
Methylation of CpG islands in the genome, Un-methylated/methylated genes, DNA methylation and gene relationship, Methylation of transcription start sites, Methylation motifs, What determines methylation state?, Methylation predicting algorithm, Methylation state at implantation, The mechanism of turning off genes, Tissue specific methylation, De novo methylation events, Methylation and gene activity, The polycomb mark, Abnormal methylation in cancer, Methylation of proliferative cells, Methylation as a function of age
Reviewed at 2020/07/12